2023
DOI: 10.3390/su15065038
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Organic Amendments Based on Garden Waste for Microbial Community Growth in Coastal Saline Soil

Abstract: Garden waste compost (GWC) has been applied as an amendment to improve the desalination efficiency, nutrient availability and diversity of the microbial community in coastal saline soil. Understanding the response of the microbial community to garden waste compost application is of great significance in coastal ecological restoration. Four treatments were established: CK, nonamended control; T1, application of 68 kg·m−3 garden waste compost; T2, application of 15 kg·m−3 bentonite; and T3, a mixture of garden w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 50 publications
1
0
0
Order By: Relevance
“…The utilization of modified materials has proven effective in improving soil environmental conditions, thus directly affecting microbial diversity and altering the structure of soil microbial communities. Our findings revealed significant variations in soil fungal diversity under different simulated modified materials; in contrast, the same was not observed in the bacterial diversity, consistent with previous findings ( Li et al, 2023 ; Zhang et al, 2023 ). In this study, we observed a significant increase in fungal diversity in response to the application of farm manure.…”
Section: Discussionsupporting
confidence: 91%
“…The utilization of modified materials has proven effective in improving soil environmental conditions, thus directly affecting microbial diversity and altering the structure of soil microbial communities. Our findings revealed significant variations in soil fungal diversity under different simulated modified materials; in contrast, the same was not observed in the bacterial diversity, consistent with previous findings ( Li et al, 2023 ; Zhang et al, 2023 ). In this study, we observed a significant increase in fungal diversity in response to the application of farm manure.…”
Section: Discussionsupporting
confidence: 91%